STAGES OF IMPROVING THE SOFTWARE AND METHODOLOGICAL SUPPORT FOR TEACHING COMPUTER SCIENCE AND ITS TEACHING METHODS (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
Today, technological progress is rapidly entering the education system. Information technologies are becoming increasingly important not only in higher education, but also at the primary education stage. Teaching informatics and information technologies starting from primary grades helps students acquire modern knowledge and skills, develop their thinking, and increase digital literacy. A number of reforms are being implemented in Uzbekistan to introduce informatics and information technologies into the education system. Despite the fact that primary school students are still young, their familiarity with technologies should be high. Because in today's modern world, technological literacy is becoming one of the main requirements for any profession. Therefore, teaching informatics and information technologies in primary education is one of the important scientific and practical issues.